EVALUATION OF INDONESIAN VERSION OF THE EMOTION WORD FLUENCY TEST - Pesau, Heni Gerda; Sulastri, Augustina; van Luijtelaar, Gilles (Faculty of Psychology, Universitas Diponegoro, 2023)
A cognitive assessment is not complete without an inspection of a client’s emotional status. The Emotion Word Fluency Test (EWFT) is a newly developed instrument for Indonesia. It provides similar assessment to other semantic word fluency tasks, linguistic and memory skills, and also a client’s current emotional standing and previously experienced emotions. Our study aims to present the newly-developed EWFT and its scoring system, and the psychometric properties of the test including its test-retest reliability and construct validity, as well as the reliability of the scoring system. Healthy participants with no history of brain-related diseases (n = 98), varying in age and education, were recruited; an additional group (n = 30) was included in the test-retest reliability study. The construct validity was evaluated with a phonemic verbal fluency test (pVFT). The EWFT was correlated (.51-.56) with the pVFT, and the three subscales of the pVFT correlated highly (.75-.80), indicating that the EWFT and pVFT share a common construct, but are also different. The scoring system showed excellent reliability (.86 for the number of correct generated words), and the test-retest reliability for the number of correct words was moderate (.54). Participants produced more negative than positive emotion words, t(29) = 6.33, p < .05. The correlation between the number of positive and negative emotion words was zero. Age affected the performance in both EWFT, F(3, 80) = 3.10, p < .05; and pVFT F(3, 80) = 2.47, p < .05; as was internationally reported. The EWFT scoring system is concluded reliable and the test has moderate reliability.